Self-Care Assistance Approach to Dorothea Orem Theory on Activity Daily Living Capabilities of Schzophrenic Patients at Atma Husada Mahakam Psychiatric Hospital, Samarinda - Milkhatun, Milkhatun; Rizal, Alfi Ari Fakhrur; Asthiningsih, Ni Wayan Wiwin; Sutriani, Merinda (University of Muhammadiyah Semarang, 2022)
Schizophrenia is a neurological disease that affects the patient's perception, thought processes, language, emotions, and social behavior. The clinical manifestation that often appears in schizophrenic patients is self-care deficit (DPD). One of the efforts that nurses can make is to provide nursing care based on the theoretical framework developed by Orem. It is called the self-care theory, which has a complete explanation of the concept of self-care, self-care deficits, and nursing actions to overcome problems that arise so that the patient can be independent as optimally as possible, including the independence of the caregiver (caregiver) when the patient is at home. This study used a purposive sampling technique, a quasi-experimental pre-post test without a control design. The sample used was schizophrenic patients at Atma Husada Mahakam Psychiatric Hospital Samarinda, with 30 respondents. Bivariate analysis using the Wilcoxon test. Based on the results of the Wilcoxon test, the t-value is 0.000, and the probability value (Sig.) is 0.05, so H0 is rejected. Thus, it can be concluded that self-care rehabilitation therapy by providing group activity therapy can increase the independence of schizophrenic patients. The average value of the patient's ADL ability after being given group activity therapy was 16.77, which was higher than the average value before the patient was given therapy, which was 12.27.